The relationship between work-stress, coping strategies and job performance of tutors in college of education in greater Accra and Eastern Regions of Ghana - Ladzekpo, Gershon Kofi; Nukpetsi, Alfred Doh (Research Journal in Advanced Social Sciences, 2020)
This study aimed at testing a model of which tutors’ ways of coping with stress are assumed to mediate the relationship between work-stress and job performance. It further investigated whether there were sex, age and work experience differences in perceived work-stress, coping strategies and job performance. The sample for the study consisted of 150 tutors from Colleges of Education in Greater-Accra and Eastern Regions. The methodological inquiry was quantitative research using survey design. The statistical tools employed in the study in analyzing the hypotheses included sample t-test, hierarchical regression, One-Way ANOVA and chi-square. Findings indicated that work-stress influenced job performance, and this depended on coping strategies. Based on these findings, it was recommended that principals of Colleges of Education should provide reasonably comfortable work environment for all tutors, and also to ensure clarity in the roles and responsibilities of the tutors, which in turn would help in coping with the work-stress.